Probing the physical properties of the intergalactic medium using blazars. Issue 2 (14th September 2021) - Dalton, Tony; Morris, Simon L; Fumagalli, Michele; Gatuzz, Efrain
ABSTRACT: We use Swift blazar spectra to estimate the key intergalactic medium (IGM) properties of hydrogen column density ($N\small {\rm HXIGM}$ ), metallicity, and temperature over a redshift range of 0.03 ≤ z ≤ 4.7, using a collisional ionization equilibrium model for the ionized plasma. We adopted a conservative approach to the blazar continuum model given its intrinsic variability and use a range of power-law models. We subjected our results to a number of tests and found that the $N\small {\rm HXIGM}$ parameter was robust with respect to individual exposure data and co-added spectra for each source, and between Swift and XMM–Newton source data. We also found no relation between $N\small {\rm HXIGM}$ and variations in source flux or intrinsic power laws. Though some objects may have a bulk Comptonization component that could mimic absorption, it did not alter our overall results. The $N\small {\rm HXIGM}$ from the combined blazar sample scales as (1 + z ) 1.8 ± 0.2 . The mean hydrogen density at z = 0 is n 0 = (3.2 ± 0.5) × 10 −7 cm −3 . The mean IGM temperature over the full redshift range is log( T /K) =6.1 ± 0.1, and the mean metallicity is [ X /H] = −1.62 ± 0.04( Z ∼ 0.02). When combining with the results with a gamma-ray burst (GRB) sample, we find the results are consistent over an extended redshift range of 0.03 ≤ z ≤ 6.3. Using our model for blazars and GRBs, we conclude that the IGM contributes substantially to the total absorption seen in both blazar and GRB spectra.